Cross-band fusion and wide-narrow integrated wireless private network oriented electric service access - Weiping SHAO; Yang LU; Jianqi LI; Ping MA; Donglei ZHANG (Dianxin kexue)
The communication requirements of electric wireless private network were analyzed,and the core idea of cross-band fusion and wide-narrow integrated wireless private network oriented electric service access was proposed,meeting the needs ofmultiple service access simultaneously,such as high speed broadband services,low delay and high reliability services,as well as wide coverage and large connection services.Research shows that cross band fusion based wireless private network has the advantages of both LTE230 and LTE1800,and it canmeet the needs of broadband and narrowband service access in the power grid.The implementation of the related schemes is necessary and feasible,which provides support foRthe further application of the electric wireless private network.